This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: How to Guess What to Prove Sometimes formulating P ( n ) is straightforward; some times its not. This is what to do: Compute the result in some specific cases Conjecture a generalization based on these cases Prove the correctness of your conjecture (by induc tion) 1 Example Suppose a 1 = 1 and a n = a d n/ 2 e + a b n/ 2 c for n > 1. Find an explicit formula for a n . Try to see the pattern: a 1 = 1 a 2 = a 1 + a 1 = 1 + 1 = 2 a 3 = a 2 + a 1 = 2 + 1 = 3 a 4 = a 2 + a 2 = 2 + 2 = 4 Suppose we modify the example. Now a 1 = 3 and a n = a d n/ 2 e + a b n/ 2 c for n > 1. Whats the pattern? a 1 = 3 a 2 = a 1 + a 1 = 3 + 3 = 6 a 3 = a 2 + a 1 = 6 + 3 = 9 a 4 = a 2 + a 2 = 6 + 6 = 12 a n = 3 n ! 2 Theorem: If a 1 = k and a n = a d n/ 2 e + a b n/ 2 c for n > 1, then a n = kn for n 1. Proof: By strong induction. Let P ( n ) be the statement that a n = kn . Basis: P (1) says that a 1 = k , which is true by hypothe sis. Inductive step: Assume P (1) , . . . , P ( n ); prove P ( n +1). a n +1 = a d ( n +1) / 2 e + a b ( n +1) / 2 c = k d ( n + 1) / 2 e + k b ( n + 1) / 2 c [Induction hypothesis] = k ( d ( n + 1) / 2 e + b ( n + 1) / 2 c ) = k ( n + 1) We used the fact that d n/ 2 e + b n/ 2 c = n for all n (in particular, for n + 1). To see this, consider two cases: n is odd and n is even. if n is even, d n/ 2 e + b n/ 2 c = n/ 2 + n/ 2 = n if n is odd, suppose n = 2 k + 1 d n/ 2 e + b n/ 2 c = ( k + 1) + k = 2 k + 1 = n This proof has a (small) gap: We should check that d ( n + 1) / 2 e n 3 In general, there is no rule for guessing the right inductive hypothesis. However, if you have a sequence of numbers r 1 , r 2 , r 3 , . . . and want to guess a general expression, here are some guidelines for trying to find the type of the expression (exponential, polynomial): Compute lim n r n +1 /r n if it looks like lim n r n +1 /r n = b / { , 1 } , then r n probably has the form Ab n + . You can compute A by computing lim n r n /b n Try to compute the form of by considering the sequence r n Ab n ; that is, r 1 Ab, r 2 Ab 2 , r 3 Ab 3 , . . . lim n r n +1 /r n = 1, then r n is most likely a polyno mial. lim n r n +1 /r n = 0, then r n may have the form A/b f ( n ) , where f ( n ) /n f ( n ) could be n log n or n 2 , for example Once you have guessed the form of r n , prove that your guess is right by induction. 4 More examples Come up with a simple formula for the sequence 1 , 5 , 13 , 41 , 121 , 365 , 1093 , 3281 , 9841 , 29525 Compute limit of r n +1 /r n : 5 / 1 = 5 , 13 / 5 2 . 6 , 41 / 13 3 . 2 , 121 / 41 2 . 95 , . . . , 29525 / 9841 3 . 000 Guess: limit is 3 ( r n = A 3 n + ) Compute limit of r n / 3 n : 1 / 3 . 33 , 5 / 9 . 56 , 13 / 27 . 5 , 41 / 81 . 5 , . . . , 29525 / 3 10 . 5000 Guess: limit is 1 / 2 ( r n = 1 2 3 n + )+ Compute r n...
View
Full
Document
This note was uploaded on 05/21/2009 for the course CS 2800 taught by Professor Selman during the Spring '07 term at Cornell University (Engineering School).
 Spring '07
 SELMAN

Click to edit the document details